Fenomena Fast Fashion dan Dampaknya Terhadap Lingkungan: (Kajian dengan Pendekatan Tafsir Interdisipliner) - Rizky Ripaldi; Abdul Fatah (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
The fast fashion industry has had a significant impact on various aspects of life, ranging from environmental degradation to social injustice. This study aims to provide a comprehensive understanding of the negative impacts of fast fashion and to propose an interdisciplinary exegesis approach to address these issues. Through this approach, the principles of simplicity, justice, and social responsibility in Islam serve as the foundation to encourage Muslim communities to make wiser choices in selecting and using fashion products. This study also emphasizes the importance of active contributions by individuals and Muslim communities in environmental conservation and social welfare enhancement. The findings of this research are expected to serve as a practical and inspirational guide for society in fostering a more ethical and sustainable lifestyle.